1999
DOI: 10.1364/ol.24.000593
|View full text |Cite
|
Sign up to set email alerts
|

Multiwave coupling in a high-gain photorefractive polymer

Abstract: The characteristics of a new high-gain photorefractive polymer composite with a PNP chromophore are investigated. Competition between beam fanning and two-wave coupling (TWC) is predicted and verified experimentally. The intensity dependence of TWC gain is studied. Higher diffraction order and forward phase conjugation in a TWC geometry are observed and explained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 7 publications
0
9
1
Order By: Relevance
“…The device with a thickness of 100 m has a gain coefficient ⌫ of 32.5 cm Ϫ1 under an applied field E 0 ϭ50 V/m. Its gain coefficient ⌫ is higher than that of the sandwich-structure device in the previous study 11 because the electric field vector and the grating vector are collinear each other. The beam-coupling ratio ␥ becomes higher for thicker devices.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…The device with a thickness of 100 m has a gain coefficient ⌫ of 32.5 cm Ϫ1 under an applied field E 0 ϭ50 V/m. Its gain coefficient ⌫ is higher than that of the sandwich-structure device in the previous study 11 because the electric field vector and the grating vector are collinear each other. The beam-coupling ratio ␥ becomes higher for thicker devices.…”
Section: Resultscontrasting
confidence: 54%
“…The photorefractive polymer consists of a mixture of a nonlinear optical chromophore, (s)-(-)-N-͑5-nitro-2-pyridyl͒prolinol, a photoconductive polymer, poly ͑N-vinylcarbazole͒, a plasticizing agent, 9-ethylcarbazole, and a sensitizing agent, 2,4,7-trinitro-9-fluorenone, with a weight ratio of 50:33:16:1. 11 To fabricate a͒ Electronic mail: hayasaki@opt.tokushima-u.ac.jp the device, the four materials are first codissolved in chloroform to form a viscous solution. Two aluminum electrodes are then bonded onto glass substrates using an adhesive agent and the glass substrates are separated by 100 m. The viscous solution is casted on the glass substrate with the two electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…al [3] have investigated the characteristics of a new high-gain photorefractive polymer composite of PNP:PVK:ECZ:TNF, 50:33: 16: 1 wt%. Competition between beam fanning and two-wave coupling was predicted theoretically and verified experimentally in [4]. They also observed higher order diffraction and phase conjugation in a twowave coupling (TWC) geometry.…”
Section: Theorymentioning
confidence: 72%
“…In most experimental setups, the -2 diffraction order exceeds the critical angle and travels in the waveguide mode [3J. In the same study [4] a series of equations were derived that describe the intemction between the different waves in the material, A1, A., A2, A2, I (beam fanning), in the TWC coupling geometry. In this paper, the equations are presented without derivation The equations that describe the interaction are: …”
Section: Theorymentioning
confidence: 99%
“…Higher order generation from self-diffraction is similar to Raman-Nath diffraction [6]. The evolution of higher orders has been explained by Solymar et al [7] and their occurrence during wave mixing in PR polymers [8]. Higher order diffraction has been studied not only for interacting beams but also for images created by an SLM, and has been shown that it is useful for image amplification, reduction and rotation [9].…”
Section: Introductionmentioning
confidence: 93%